Pengembangan Media Pembelajaran Komik Berbasis Budaya Lokal Minangkabau untuk Penguatan Karakter Pelajar Pancasila - Enjoni, Enjoni; Sayuti, Muhammad; Desfitri, Eni; Effendi, Heri (Journal of Moral and Civic Education, 2023)
This research is entitled Development of Learning Media Using Comics Based on Local Minangkabau Culture to Strengthen Character According to Pancasila Student Profiles of Grade V Students at Elementary School in Padang City. This research was carried out in three stages, namely: Preliminary Research, Prototyping Phase and Assessment Phase. The subjects of this research data trial were fifth grade elementary school students, totaling 52 students, obtained by observation, assessment sheets, observations, tests and questionnaires. Field trials were carried out by 3 validators who were considered experts. The practicality of teacher and student responses was tested with three school categories namely: High, Medium and Low. Data analysis in the form of a questionnaire was carried out descriptively about the impact of local culture-based comic media. Test analysis using Anava. The analysis phase begins with a review with pedagogical experts, linguists and media design experts, as well as field trials with large groups. Expert validation results with very valid categories with an average of 94.99%. Meanwhile, according to the teacher, the practicality aspect is in the very practical category with a percentage of 93.33%. While the practicality test according to students is in the very practical category with an average of 89.51% in the three schools. Thus this research is included in the category of valid, practical and effective.